1996
DOI: 10.1046/j.1471-4159.1996.67010064.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Apoptosis‐Effector Gene, Bax, Is Up‐Regulated in Vulnerable Hippocampal CA1 Neurons Following Global Ischemia

Abstract: The observation that delayed death of CAl neurons after global ischemia is inhibited by protein synthesis inhibitors suggests that the delayed death of these neurons is an active process that requires new gene expression. Delayed death in CAl has some of the characteristics of apoptotic death; however, candidate proapoptotic proteins have not been identified in the CAl after ischemia. We studied the expression of Bax protein and mRNA, a member of the bcl-2 family that is an effector of apoptotic cell death, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(110 citation statements)
references
References 21 publications
(34 reference statements)
10
94
1
5
Order By: Relevance
“…In vitro studies have demonstrated that hypoxia in the brain following focal and global ischemia can trigger programmed cell death (26,27). Herein, a significant number of TUNEL-positive cells were observed in the ischemic regions in rats with MCAO for 2 h followed by reperfusion for 24 h. Caspase-3 is well-known as an executioner of apoptosis, and there is a significant body of evidence that activation of caspase-3 is observed after ischemic injury.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro studies have demonstrated that hypoxia in the brain following focal and global ischemia can trigger programmed cell death (26,27). Herein, a significant number of TUNEL-positive cells were observed in the ischemic regions in rats with MCAO for 2 h followed by reperfusion for 24 h. Caspase-3 is well-known as an executioner of apoptosis, and there is a significant body of evidence that activation of caspase-3 is observed after ischemic injury.…”
Section: Discussionmentioning
confidence: 93%
“…The attenuation of lethal ischemia-induced DNA fragmentation by a conditioning ischemia-induced Bcl-2 and Bcl-xl overexpression indicates that Bcl-2 family proteins may take part in protective ischemic preconditioning induced by sublethal forebrain ischemia. In many experimental paradigms, level changes in the Bcl-2 family genes have been reported as early as 6 to 8 hours in hippocampus after lethal ischemia, [17][18][19] but the increased Bcl-2, Bcl-xl, and Bax mRNA levels were not consistent with protein levels, probably because of the decreased protein synthesis due to lethal ischemia. 20,21 In our experiment the Bcl-2 family mRNA level changes are observed to be consistent with those of the proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, at the periphery of the ischemic core with focal insults, or in selectively vulnerable regions such as the hippocampus CA1 after a short period of ischemia, neurons may die over a longer period with morphological signs and biological features indicative of apoptosis (67,112). In this section, emphasis is placed on the welldocumented notion that an effective suppression of apoptosis is associated with brain tolerance.…”
Section: E Control Of Cell Death/survivalmentioning
confidence: 99%